Inter-procedural analysis for parallel computing - Mohd-Saman, M.Y.; Evans, D.J. (Elsevier, 1995)
Numerous efforts have been made on performing data dependence analysis on sequential programs and to parallelize them, especially the loops. However, program restructurers often have to make some conservative assumptions whether to parallelize them or not, due to insufficient information caused by procedure calls. Procedures that are called may be modifying some global variables and this inhibits any parallelism. This paper discusses the Inter-procedural analysis (IPA) based on the Bernstein Method [29]. IPA involves in collecting information regarding a procedure call and the effects of usage of variables in the body of the called procedure. A way to handle inter-procedural information by using the Bernstein Sets [10] is proposed. © 1995.